2017
DOI: 10.29245/2572-9411/2017/3.1103
|View full text |Cite
|
Sign up to set email alerts
|

SCID pigs: An emerging large animal NK model

Abstract: Severe Combined ImmunoDeficiency (SCID) is defined as the lack or impairment of an adaptive immune system. Although SCID phenotypes are characteristically absent of T and B cells, many such SCID cellular profiles include the presence of NK cells. In human SCID patients, functional NK cells may impact the engraftment success of life saving procedures such as bone marrow transplantation. However, in animal models, a T cell-, B cell-, NK cell+ environment provides a valuable tool for asking specific questions abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The advantage of the pig model is its similarity to humans in genetic makeup, anatomy, and physiology. Previous studies have demonstrated that analyzed parameters of pig immune system are 80% similar to human, while there is only a 10% similarity between human and mouse (2, 80, 81). The SCID mouse is widely used because of the generation of the humanized model in which HSCs cells are induced to a given SCID host to permit the differentiation of elements involved in the immune system (82).…”
Section: Resemblance Of Human To Mouse and Pigmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage of the pig model is its similarity to humans in genetic makeup, anatomy, and physiology. Previous studies have demonstrated that analyzed parameters of pig immune system are 80% similar to human, while there is only a 10% similarity between human and mouse (2, 80, 81). The SCID mouse is widely used because of the generation of the humanized model in which HSCs cells are induced to a given SCID host to permit the differentiation of elements involved in the immune system (82).…”
Section: Resemblance Of Human To Mouse and Pigmentioning
confidence: 99%
“…Researchers have tried to extend the applicability of the pig model due to similarity of pig’s immune system to human. Several SCID pig models have already been generated (2, 83). A humanized pig disease model as a research platform will be a breakthrough that can transform preclinical research because it is the closest animal model to human.…”
Section: Resemblance Of Human To Mouse and Pigmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of the SCID pig provides an interesting avenue for studying the role of NK cells in both allogeneic and xenogeneic anti-tumor responses in a large animal model (67). Similarly to human NK cells, swine NK cells can be identified by expression of CD3 − CD16 + CD56 + surface markers (68).…”
Section: Swine As a Pre-clinical Model To Test Biological And Cellulamentioning
confidence: 99%